2019
DOI: 10.1021/jacs.8b13123
|View full text |Cite
|
Sign up to set email alerts
|

Microsolvation of the Redox-Active Tyrosine-D in Photosystem II: Correlation of Energetics with EPR Spectroscopy and Oxidation-Induced Proton Transfer

Abstract: Photosystem II (PSII) of oxygenic photosynthesis captures sunlight to drive the catalytic oxidation of water and the reduction of plastoquinone. Among the several redox-active cofactors that participate in intricate electron transfer pathways there are two tyrosine residues, Y Z and Y D . They are situated in symmetry-related electron transfer branches but have different environments and play distinct roles. Y Z is the immediate oxidant of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 144 publications
(347 reference statements)
1
19
0
Order By: Relevance
“…182 Similar correlations derived from quantum chemical studies have been essential for probing the hydration and uncovering the structural basis of spectroscopic observations for the other redox-active tyrosine of PSII, Y D . 183 Intriguingly, the above observations suggest a direct role for Ca in structuring the hydrogen-bonding environment of Y Z and hence directly modulating its redox properties, 182 which is crucial for ensuring efficient coupling between the manganese cluster of the OEC and the charge-separation site (reaction centre) of PSII. Complementing this hypothesis, explicit calculations of the effect of calcium substitution by various redox-inactive cations showed that the redox potential of the OEC responds only to the total charge of the cation while remaining insensitive to its Lewis acidity, 190 in contrast to correlations established for synthetic complexes.…”
Section: Corresponds Very Well With the 55 Mnmentioning
confidence: 96%
See 1 more Smart Citation
“…182 Similar correlations derived from quantum chemical studies have been essential for probing the hydration and uncovering the structural basis of spectroscopic observations for the other redox-active tyrosine of PSII, Y D . 183 Intriguingly, the above observations suggest a direct role for Ca in structuring the hydrogen-bonding environment of Y Z and hence directly modulating its redox properties, 182 which is crucial for ensuring efficient coupling between the manganese cluster of the OEC and the charge-separation site (reaction centre) of PSII. Complementing this hypothesis, explicit calculations of the effect of calcium substitution by various redox-inactive cations showed that the redox potential of the OEC responds only to the total charge of the cation while remaining insensitive to its Lewis acidity, 190 in contrast to correlations established for synthetic complexes.…”
Section: Corresponds Very Well With the 55 Mnmentioning
confidence: 96%
“…Quantum chemical studies that focus on spectroscopic properties have also helped to elucidate critical aspects of the redox-active tyrosine Y Z and Y D residues. 182,183 Here it is the g-tensor of the tyrosyl radical that is the central spectroscopic parameter. This can be calculated with standard DFT approaches, although particular care has to be taken to ensure that the calculations correctly represent the electronic structure of both the Y Z radical and the Mn cluster.…”
Section: Corresponds Very Well With the 55 Mnmentioning
confidence: 99%
“…This is supported by recent computational studies that predict a remarkably short H-bond between Y Z and D1-His190, which is in agreement with the X-ray crystal structure of PSII ( Saito et al., 2011 ; Umena et al., 2011 ). Additionally, quantum mechanical (all-QM) and hybrid quantum mechanical/molecular modeling (QM/MM) studies have suggested that the protonation state of the conjugate base, microsolvation, and hydrogen bonding could influence the redox activity of Y D and Y Z ( Ahlbrink et al., 1998 ; Chai et al., 2019 ; Saito et al., 2011 ; Sirohiwal et al., 2019 ). Since the Y Z ⋅ radical intermediate is short lived, previous mechanistic proposals for PCET were based on the dark-stable Y D ⋅ radical that displays slower decay kinetics.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Of particular interest is water involvement in electron transfer processes, 2 5 its action as a proton wire 6 8 or its role in proton-coupled electron transfer (PCET). 9 12 The identification of internal water in proteins can be achieved by X-ray diffraction. 13 15 However, the crystallization of transient protein complexes is difficult.…”
mentioning
confidence: 99%
“…The lack of evidence for a second, almost equivalent water H-bonded to Y 356 • strongly suggests that the two-water model has become very unlikely and alternative explanations for the shifted g x value of Y 356 • will have to be examined. The precise location of second-sphere residues might play a role, 12 which will require further experimental and computational investigation.…”
mentioning
confidence: 99%